Learning from experience : minority identities, multicultural struggles - Moya, Paula M. L. (University of California Press, 2002)
In Learning from Experience, Paula Moya offers an alternative to some influential philosophical assumptions about identity and experience in contemporary literary theory. Arguing that the texts and lived experiences of subordinated people are rich sources of insight about our society, Moya presents a nuanced universalist justification for identity-based work in ethnic studies.